PENGARUH MODEL PEMBELAJARAN AIR (AUDITORY, INTELLECTUALLY, REPETITION) TERHADAP PEMAHAMAN KONVERSI SATUAN PANJANG SISWA SEKOLAH DASAR (SD) - Simanjuntak, Putri Caryn Malsanda; Maulana, Maulana; Irawati, Riana (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
Mathematics learning in unit length conversion is still a problem that must be solved at SDN Ganeas I and II. The students still can't understand the concept of unit length conversion correctly. Therefore, in the learning activities, need a new innovations learning models. This research purpose to determine AIR (Auditory, Intelectually, Repetition) learning model on the concept of length unit conversion for students grade IV of elementary school.The research method used is a quasi-experiment with a non-equivalent control group research design. Data collection with observation and tests.The tests used are pretest and posttest, the sample was grade IV students SDN Ganeas II as the experimental class and grade IV students of SDN Ganeas I as the control class.Data processing techniques using normality tests, homogenenity, t-tests, Mann withney tests, normalized gain tests, with the help of SPSS 26.The results of the study, with using the Mann-Whitney test obtained a p-value of 0.000<0.005,then H0 is rejected and H1 is accepted, so it is concluded that there is an improvement in students' abilities with the AIR (Auditory, Intelectually, Repetition) learning model.